2016
DOI: 10.1002/dc.23623
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐needle aspiration biopsy of prostate synovial sarcoma: A case report and review of the literature

Abstract: We describe a case of synovial sarcoma originating from prostate gland. The diagnosis was confirmed by fluorescent in situ hybridization analysis (FISH) for SYT rearrangement on the cell block. Synovial sarcoma is a high grade soft tissue malignancy with exceedingly rare involvement of genitourinary tract. However this entity should be considered in the differential diagnosis when dealing with aspiration biopsies of particularly deep seated lesions with spindle cell or small round blue cell cytomorphology. Dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…[1][2][3][4] There are a few case reports of synovial sarcoma diagnosed based on FNA biopsy. [5][6][7][8][9][10][11][12][13][14][15][16] The cases described involved widespread locations such as heart, thyroid, kidney, prostate, large vessels, parapharyngeal space, axilla, and lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] There are a few case reports of synovial sarcoma diagnosed based on FNA biopsy. [5][6][7][8][9][10][11][12][13][14][15][16] The cases described involved widespread locations such as heart, thyroid, kidney, prostate, large vessels, parapharyngeal space, axilla, and lower extremity.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported that the SYT-SSX fusion transcripts are not only a definitive diagnostic marker of SS, but also yield important independent prognostic information (6). It was reported that a patient with a SS bearing the SYT-SSX2 translocation had a better prognosis compared with a patient bearing the SYT-SSX1 translocation (7,8). This conclusion was supported by a multi-institutional retrospective study of 243 SS patients by Ladanyi et al (9).…”
Section: Discussionmentioning
confidence: 91%
“…Four of the five patients appear to have died of respiratory failure in the setting of pulmonary metastases. 7,13,14,16 On the basis of this very limited data set, the longest reported survival for patients with known metastatic prostatic synovial sarcoma is approximately 3 years after initial diagnosis. Clinical follow-up for our patient is still ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…In the time since Iwasaki and colleagues described the first known case of primary prostatic synovial sarcoma in 1999, only 11 total cases have been reported in the English literature to date. [7][8][9][10][11][12][13][14][15][16] We herein present what we believe is the 12th reported case of primary prostate synovial sarcoma on the basis of the published literature, and to our knowledge is only the second reported case of primary synovial sarcoma of the prostate with pulmonary metastatic disease at presentation.…”
Section: Introductionmentioning
confidence: 97%